2021
DOI: 10.3892/ijmm.2021.5036
|View full text |Cite
|
Sign up to set email alerts
|

CAPN3: A muscle‑specific calpain with an important role in the pathogenesis of diseases (Review)

Abstract: Calpains are a family of Ca 2+ -dependent cysteine proteases that participate in various cellular processes. Calpain 3 (CAPN3) is a classical calpain with unique N-terminus and insertion sequence 1 and 2 domains that confer characteristics such as rapid autolysis, Ca 2+ -independent activation and Na + activation of the protease. CAPN3 is the only muscle-specific calpain that has important roles in the promotion of calcium release from skelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 112 publications
0
18
0
Order By: Relevance
“…We then compared the expression of Foxo1 , Foxo3 , Fbxo32 (atrogin -1 ), and Trim63 ( MuRF1 ), which is upregulated in response to skeletal muscle atrophy, including cachexia, denervation, and disuse muscle atrophy 33 , 34 . We also compared the expression of the Ca 2+ ‑dependent cysteine proteases, Capn1 and Capn3 , as recessive mutations in these genes cause muscular dystrophy 35 , 36 . No significant differences were found in the gene expression profiles between MG and PG mice in any mission (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We then compared the expression of Foxo1 , Foxo3 , Fbxo32 (atrogin -1 ), and Trim63 ( MuRF1 ), which is upregulated in response to skeletal muscle atrophy, including cachexia, denervation, and disuse muscle atrophy 33 , 34 . We also compared the expression of the Ca 2+ ‑dependent cysteine proteases, Capn1 and Capn3 , as recessive mutations in these genes cause muscular dystrophy 35 , 36 . No significant differences were found in the gene expression profiles between MG and PG mice in any mission (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, cysteine and glycine-rich protein 3 ( CSRP3 ), also known as muscle LIM protein (MLP), which promotes fast-twitch muscle fiber formation in chickens, showed significantly decreased mRNA expression post miR-499-5p overexpression ( Shan et al, 2022 ). Calpain 3 ( CAPN3 ) is the only muscle-specific calpain that has impotant role in muscle function such as muscle formation and remodeling ( Chen et al, 2021 ). Studies have indicated that mutations in CAPN3 are associated with meat quality traits including muscle fiber composion in chicken and pig ( Gandolfi et al, 2011 ; Felício et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The calpain family in humans consists of 15 members and all are Ca 2+ -dependent, non-lysosomal cysteine proteases ( Chen et al, 2021 ). Unlike other proteases that catalyse the degradation of their substrates, calpains recognize and proteolyze their substrates, but do not degrade them ( Ono and Sorimachi, 2012 ).…”
Section: Mechanisms Of Protein Quality Controlmentioning
confidence: 99%